1978
DOI: 10.1161/01.cir.58.6.1023
|View full text |Cite
|
Sign up to set email alerts
|

Disparate electrophysiological alterations accompanying dysrhythmia due to coronary occlusion and reperfusion in the cat.

Abstract: The electrophysiologic changes associated with dysrhythmias induced by coronary occlusion and by subsequent reperfusion were characterized with six complimentary approaches in chloralose-anesthetized cats (n = 57) with proximal occlusion of the left anterior descending (LAD) coronary artery. Occlusion led to reproducible ventricular dysrhythmia which abated in 35 minutes. The electrophysiologic effects of reperfusion initiated at this time could be studied. Simultaneous bipolar electrograms (epi-, myo- and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(42 citation statements)
references
References 51 publications
3
39
0
Order By: Relevance
“…Since reentry is dependent ) upon slowed conduction, and reperfusion rapidly reverses the ischemic induced conduction delav, these observations would initially appear to negate a reentrant mechanism for reperfusion arrhythmias. Indeed, the similar finding of a rapid improvement in conduction after 35 minutes of coronary occlusion was taken as strong evidence against a reentrant mechanism in the feline model of reperfusion arrhythmias (9). However, although conduction improves with reperfusion, in those areas of the heart rendered unresponsive by ischemia, the conduction improvement Ventricular automaticity was assessed in five dogs during reperfusion after complete atrioventricular (AV) block was produced by injecting formalin into the AV node according to the method described bv Loeb et a 1 ( 71).…”
Section: Flow Determinants Of Reperfusion Arrhythmiasmentioning
confidence: 82%
“…Since reentry is dependent ) upon slowed conduction, and reperfusion rapidly reverses the ischemic induced conduction delav, these observations would initially appear to negate a reentrant mechanism for reperfusion arrhythmias. Indeed, the similar finding of a rapid improvement in conduction after 35 minutes of coronary occlusion was taken as strong evidence against a reentrant mechanism in the feline model of reperfusion arrhythmias (9). However, although conduction improves with reperfusion, in those areas of the heart rendered unresponsive by ischemia, the conduction improvement Ventricular automaticity was assessed in five dogs during reperfusion after complete atrioventricular (AV) block was produced by injecting formalin into the AV node according to the method described bv Loeb et a 1 ( 71).…”
Section: Flow Determinants Of Reperfusion Arrhythmiasmentioning
confidence: 82%
“…[17][18][19][20] Other studies, using either coronary artery ligation or reperfusion models, have also suggested that a large and variable number of animals do not develop ventricular fibrillation, even without prior antiarrhythmic therapy (approximately 60% and 30%, respectively).2 29 Previous studies in this laboratory, however, indicate that the risk for developing ventricular fibrillation on reperfusion might be predicted for individual animals based on the incidence, time course and severity of arrhythmias occurring during the antecedent period of acute coronary artery ligation. 30' 31 This was predicated on the observation that different animals subjected to acute one-stage ligation of the proximal left anterior descending coronary artery developed either immediate (occurring 2-12 minutes after ligation), delayed (occurring 14-30 minutes after ligation), both types or no ventricular arrhythmias at all;32' 33 and that the risk for ventricular fibrillation during the subsequent period of coronary artery reperfusion correlated closely with the occurrence of these ligation arrhythmias.…”
mentioning
confidence: 99%
“…It is well known that transient coronary artery occlusion can lead to malignant ventricular arrhythmia during ischaemia and reperfusion (Penkoske et al, 1978;Janse & Kle ber, 1981;Ferrier et al, 1985). The mechanism(s) underlying the genesis of these lethal arrhythmias (ventricular tachycardia and ventricular ®brillation) are complex but may include the reentry and the oscillatory afterpotentials (Manning & Hearse, 1984;Ferrier et al, 1985;Pogwizd & Corr, 1987).…”
Section: Discussionmentioning
confidence: 99%